EMPHASIS AND ADVOCACY IN ANNOTATING AND TRANSLATING THE BIBLE - C.W. Stenschke (Acta Theologica)
The past decades have seen several editions of the Bible with distinct emphases. Examples of such special-audience editions of the Bible are particularly aimed at women, men or young people. There are also particular “Bibles”, or parts thereof, for bikers, for instance, or a Bible edition that highlights verses concerning issues of justice. The vast majority of these Bible editions, which try to address a particular audience or promote/advocate a certain cause, offer their particular emphases in the text and notes in the margins, but do not actually interfere with the text itself. However, there are also editions of the Bible, where the editors/translators introduce particular emphases in their actual rendering of the biblical text itself. The Complete Jewish Bible is one of the examples to be discussed in some detail in this instance. This article describes these approaches and assesses their validity.